Porcine circovirus type 2 and its associated diseases in southwestern Nigeria: Farmers’ perception and level of awareness (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: Porcine circovirus type 2 (PCV2) is one of the most important causative agents of swine diseases that pose a global economic threat. Presently, there is little or no information on the perception and awareness of PCV2 and its associated effects among pig farmers in Nigeria. Therefore, this research was carried out to describe pig farmers’ views, awareness, and likely impact of PCV2 and its associated postweaning multisystemic wasting syndrome (PMWS) on pig production in the southwestern region of Nigeria. Materials and Methods: A cross-sectional survey of pig farmers in Oyo and Ogun states, Southwest Nigeria, was carried out with the help of a self-administered questionnaire. Results: A total of 111 farms out of the 385 required took part in the study, resulting in a total response rate of 28.8%. 89 (79.2%, 95% CI = 70.8–85.8) pig farmers who participated were unaware of PCV2, while 46 (41.4%, 95% CI = 32.7–50.7) had heard about PMWS. The level of awareness was generally poor, with an average score of 1.43 (SD ± 1.25; 23.9%). Only 23% (25/111) of the participants had a high level of awareness. To promote awareness about PCV2/PMWS, participants’ most preferred sources of information were seminars, extension services (especially by veterinary and agricultural extension officers), social media (WhatsApp and YouTube), and mobile telephone (through calls or text messages). Conclusions: The present study showed a gap in the level of farmers’ awareness about PCV2/ PMWS, and to bridge the gap, more scientific-based evidence is needed to promote targeted educational programs and policy formulations. Also, with the dearth of information about PCV2, it is necessary to determine its prevalence and the characteristics of the virus possibly circulating within the swine herds in Nigeria.J. Adv. Vet. Anim. Res., 9(2): 203–210, June 2022http://doi.org/10.5455/javar.2022.i585